Impact of Ligand Exchange on Gold Nanostars’ Reshaping, Stabilization, Photothermal Efficiency, and Cell Viability - Melo-Hurtado, F (American Chemical Society, 2024)
Gold nanostars (AuNSs) have achieved special relevance for potential biomedical applications, e.g., in theranostics. In relation to this, some authors have explored controlling the conditions that trigger structural and morphological changes in these structures. In this work, we studied conditions that can trigger morphological changes of AuNSs or maintain their stability, such as ligand exchange to nonthiolated and thiolated species. First, the synthesis stabilizing ligand of AuNS, 4-(2-hydroxyethyl)-1-piperazinapropanesulfonic acid (EPPS), was exchanged for nonthiolated species to trigger or prevent morphological changes. One of these species, triphenylphosphine-monosulfonate (TPPMS), generated a stable and unexplored nanostructure even at acidic pH, with interaction mediated mainly by aromatic groups and the phosphine moiety, in comparison to hexadecyltrimethylammonium bromide (CTAB) and citrate, which are ligands that trigger morphological changes of AuNS. Moreover, TPPMS-coated AuNSs can be exchanged by thiolated species, such as carboxylated poly(ethylene glycol) (HS-PEG-COOH), offering more versatility through covalent strategies. In addition, properties related to the application of these stabilized AuNSs were explored, such as photothermia and biocompatibility. The photothermal transduction efficiency and cell viability of AuNSs coated with EPPS, TPPMS, and PEG-COOH were evaluated, showing a temperature increment of the colloidal solutions and optimal mitochondrial activity. We believe that this work contributes to understanding the phenomena and conditions that trigger changes in the morphology or stability of AuNSs and that AuNSs coated with TPPMS and PEG-COOH possess optimal properties for potential biomedical applications. © 2023 American Chemical Society